Biodegradation of methylene blue by bacteria strains isolated from contaminated soil - Fazilah Ariffin,; Nur Eqa Mardihah Che Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Methylene blue is one of the textile dyes that are commonly used in the textile coloring industry. The discharge of textile wastewater containing residual textile coloring substances into the environment can lead to environmental pollution. Thus, bioremediation can be a solution to reduce dye pollution by using bacterial strains. In the present study, two bacterial strains with the ability to degrade methylene blue dye were isolated from contaminated soil. Both isolated bacteria were further evaluated for the dye decolorization percentage and the effect of abiotic parameters on bacterial growth. The isolated bacteria were incubated in a mineral salt medium added with methylene blue dye for eight days in static aerobic conditions. The dye degradation was examined by using UV-VIS spectrophotometer at 665 nm. The isolated bacteria were identified as Klebsiella pneumoniae strain UMTFA1 (EK) and Pseudomonas aeruginosa strain UMTFA2 (EP) using 16s rRNA sequencing. The biodegradation study showed that Klebsiella pneumoniae strain UMTFA1 (EK) and Pseudomonas aeruginosa strain UMTFA2 (EP) were capable to degrade 10.52% and 11.65% of methylene blue dye after 8 days of incubation, respectively. The present study may provide a basis for biotreatment and bioremediation of dye-contaminated soils.